2002
DOI: 10.1046/j.1365-2141.2002.03815.x
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin's disease in the elderly: a population‐based study

Abstract: Summary. This study evaluated the incidence and outcome of Hodgkin's disease (HD) in older patients using a population-based approach. In total, 102 patients (52 men, 50 women) aged ‡ 60 years presented in the Northern Health Region of England (population of 3AE09 million) between 1 January 1991 and 31 December 1998 and were studied prospectively. The age-specific incidence was 1AE97/ 100 000 for those aged 60-69 years, and 2AE18/100 000 for those aged 70 years or over. The median age of the cohort was 70 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
95
1
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(111 citation statements)
references
References 29 publications
12
95
1
3
Order By: Relevance
“…Some of the interstudy variation may be attributable to the different epidemiologic features of the disease in different geographic settings and some may be related to case selection. Three previous population-based studies have demonstrated that EBV-associated cases have a poorer prognosis: one was relatively small, 11 and although EBV-positive cases were found to have a poorer outcome than patients with EBV-negative disease, this difference did not reach statistical significance in this small study; one was confined to adults 60 years or older 18 ; and the third was confined to women. 17 In the latter cohort, 17 the adverse effect of EBV association was confined to patients aged 45 to 79 years.…”
Section: Introductioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Some of the interstudy variation may be attributable to the different epidemiologic features of the disease in different geographic settings and some may be related to case selection. Three previous population-based studies have demonstrated that EBV-associated cases have a poorer prognosis: one was relatively small, 11 and although EBV-positive cases were found to have a poorer outcome than patients with EBV-negative disease, this difference did not reach statistical significance in this small study; one was confined to adults 60 years or older 18 ; and the third was confined to women. 17 In the latter cohort, 17 the adverse effect of EBV association was confined to patients aged 45 to 79 years.…”
Section: Introductioncontrasting
confidence: 56%
“…[1][2][3] The impact of the tumor-cell EBV status on the prognosis of patients with HL remains controversial. Most previous studies have not reported a significant association between EBV status and outcome, [4][5][6][7][8][9][10][11] while others have found that EBV-associated cases have either a more or less favorable prognosis [12][13][14][15][16][17][18] (Table 1). Some of the interstudy variation may be attributable to the different epidemiologic features of the disease in different geographic settings and some may be related to case selection.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Clarke et al 6 and Stark et al 7 demonstrated that EBV positivity of HRS cells correlated with significantly poorer survival in HL patients aged 45-79 years of age or aged 60 years and over, respectively. Starke et al 7 also determined that EBV status had an adverse effect on clinical outcomes especially in elderly patients (70 years of age and above) compared with that in a younger elderly group (60-69 years of age). Enblad et al 8 also reported that EBV-positive CHL patients were more likely to be older, have increased B symptoms, and more advanced disease.…”
Section: Ebv-associated Classical Hodgkin Lym-phoma and Ebv-associatementioning
confidence: 99%
“…However, in population-based studies have consistently shown a noticeable survival disadvantage in EBVpositive HL especially in the case of older patients (Enblad et al, 1999;Clarke et al, 2001;Stark et al, 2002), indicating the infl uence of EBV existence in HRS cells on clinical outcome. Furthermore, the fact that an EBV transforming protein, LMP1, is expressed almost 100% in HRS cells of HL in HIV-infected patients suggests that EBV may play as a crucial etiological agent in the generation of HRS cells, at least in certain circumstances (Thompson et al, 2004;Carbone et al, 2009).…”
Section: Treatment Strategies For the Patients With Ebv-associated Chlmentioning
confidence: 99%